Hidro- & deuterocarbamoilação do alceno de Karady-Beckwith: síntese estereosseletiva da asparagina e seus derivados N4-substituídos - Moro, Pedro Augusto Marocco (2023)
The development of sustainable stereoselective methodologies for obtaining compounds of synthetic and biological relevance is highly important in contemporary times. In this regard, the synthesis of non-natural amino acids appears as a possible tool for modulating the properties of small molecules, peptides, and proteins. Visible light has been gaining increasing prominence among the methodologies used for obtaining amino acid derivatives. The use of light presents a good alternative due to its generally mild reaction conditions compared to classical thermal methodologies. Our research group has been developing photocatalytic methodologies for the synthesis of small molecules as well as amino acids and peptide modification. The present work explored the stereoselective synthesis of non-natural amino acids derived from Asparagine. Karady-Beckwith alkene was used as a radical acceptor, 4-carbamoyl dihydropyridines as a source of carbamoyl radicals, and the organophotocatalyst 4CzIPN for the preparation of 23 hydro- and deuterocarbamoylated derivatives in batch and continuous flow. The methodology allowed for the stereoselective synthesis of amino acid derivatives with good to excellent yields under mild conditions and metal-free.